Factors associated with the risk perception of COVID-19 infection and severe illness: A cross-sectional study in Japan. (June 2022) - Adachi, Megumi; Murakami, Michio; Yoneoka, Daisuke; Kawashima, Takayuki; Hashizume, Masahiro; Sakamoto, Haruka; Eguchi, Akifumi; Ghaznavi, Cyrus; Gilmour, Stuart; Kaneko, Satoshi; Kunishima, Hiroyuki; Maruyama-Sakurai, Keiko; et al.
Abstract: Understanding COVID-19 risk perception may help inform public health messaging aimed at encouraging preventive measures and improving countermeasures against the pandemic. We conducted an online survey of 29, 708 Japanese adults in February 2021 and estimated the associations between COVID-19 risk perception and a broad array of individual factors. Two logistic regressions were constructed to estimate factors associated with the risk perception of COVID-19 (defined as responding that one might become infected within the next 6 months), and of severe illness among those who responded that they might become infected (defined as responding that one would become severely ill). After adjusting for covariates, those with a higher perceived risk of the COVID-19 vaccine had higher odds of risk perception for both infection and severe illness. Interestingly, those with higher odds of risk perception of being infected were more likely to report obtaining their information from healthcare workers whereas those with lower odds were more likely to report obtaining their information from the Internet or the government; those with lower odds of risk perception of being severely ill were more likely to report obtaining their information from the Internet. The higher the trust level in the government as a COVID-19 information source, the lower the odds of both risk perception of being infected and becoming severely ill. The higher the trust levels in social networking services as a COVID-19 information source, the higher the odds of risk perception of becoming severely ill. Public health messaging should address the factors identified in our study. Highlights: Perceived risks of a COVID-19 vaccine was related to risk perception of COVID-19 infection and severe illness. Getting information from healthcare workers was related to higher risk perception of infection. Higher trust in SNS was related to higher risk perception of COVID-19 of severe illness.